(untitled) (Bangladesh Journal of Pharmacology, 2025)
This study detailed the isolation and structural elucidation of two flavan-3-ol derivatives from the ethyl acetate extract of peanut skin. Structural characterization was achieved through analysis of spectral data, including HR-ESI-MS, 1D and 2D NMR, [α]D measurement, and ECD spectra, identifying the compounds as arachiflavanol A and proanthocyanidin A2. Notably, this research marks the first time arachiflavanol A has been isolated from a natural source. Furthermore, both compounds demonstrated considerable antioxidant potential in the DPPH radical scavenging assay, with IC50 values of 0.07 µM/mL and 0.05 µM/mL, respectively, which were comparable to the IC50 value of the reference antioxidant ascorbic acid (0.04 µM/mL).